2022
DOI: 10.1038/s41598-022-23807-4
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of the dynamics of Plasmodium falciparum deoxynucleotide-triphosphate pool in a stage-specific manner

Abstract: Understanding and characterizing the molecular background of the maintenance of genomic integrity might be a major factor in comprehending the exceptional ability of the malaria parasite, Plasmodium falciparum to adapt at a fast pace to antimalarials. A balanced nucleotide pool is an essential factor for high-fidelity replication. The lack of detailed studies on deoxynucleotide-triphosphate (dNTP) pools in various intraerythrocytic stages of Plasmodium falciparum motivated our present study. Here, we focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…2 A ), suggesting its critical function beyond the hepatic stage. We observed robust UIS2 expression in trophozoites, which are characterized by extensive DNA replication and metabolic activities, including multiple rounds of nuclear division (29, 30). Previous studies have shown the absence of P-eIF2alpha in Plasmodium trophozoites (27).…”
Section: Discussionmentioning
confidence: 85%
“…2 A ), suggesting its critical function beyond the hepatic stage. We observed robust UIS2 expression in trophozoites, which are characterized by extensive DNA replication and metabolic activities, including multiple rounds of nuclear division (29, 30). Previous studies have shown the absence of P-eIF2alpha in Plasmodium trophozoites (27).…”
Section: Discussionmentioning
confidence: 85%